Caracterização física de painéis aglomerados de Eucalyptus grandis com adição de resíduos industriais madeireiros - Pierre, Fernanda Cristina [UNESP]; Ballarin, Adriano Wagner [UNESP]; Lara Palma, Hernando [UNESP] (UFLA - Universidade Federal de Lavras, 2014)
In Brazil, the wood from planted forests constitutes the main material source for the production of particleboards. The utilization of forest residues for production of these panels was not implemented in industrial level yet. This work had the objective of evaluating the physical properties of three layers particleboard, industrially manufactured, using wood of Eucalyptus grandis from plantation and industrial wood residues in different ratios (adittion from 10% to 35% in volume). The material (Eucalyptus grandis wood and industrial residues - recycled pallets and sawdust) was supplied by Eucatex S. A. Ind. e Com. located in Botucatu - Sao Paulo State, Brazil, where the panels had been manufactured in Eucatex plant. Physical tests were carried out at the Process Laboratories of Eucatex and in the Materials Testing Laboratory, Rural Engineering Department of the College of Agronomic Sciences - Sao Paulo State University - UNESP. Results revealed that panels had very good physical performance, attending, in general, to all the technical specifications established by the product standards, even in the treatments with higher addition of residues. The final moisture content of the panel presented effect in the properties studied with general trend of reduction in water absorption and swelling in thickness when the moisture content increased from 9% for 12,5%.

A madeira de florestas plantadas constitui a principal fonte de matéria-prima para produção de painéis aglomerados no Brasil. O aproveitamento dos resíduos florestais para produção desses painéis ainda não foi implementado em nível industrial. Este trabalho teve por objetivo avaliar as propriedades físicas dos painéis de madeira aglomerada (MDP - medium density particleboard) de três camadas, fabricados industrialmente na linha de produção da empresa Eucatex S.A. Indústria e Comércio, utilizando madeira de Eucalyptus grandis e resíduos industriais madeireiros (material reciclado de paletes e serragem), em diferentes proporções, variando de 10% a 35% em volume. O material foi disponibilizado pela empresa, na unidade industrial MDP localizada no município de Botucatu - SP, onde foram fabricados os painéis em escala industrial. Os ensaios físicos foram realizados no Laboratório de Processo da Eucatex e no Laboratório de Ensaios de Materiais do Departamento de Engenharia Rural da Faculdade de Ciências Agronômicas - UNESP - Botucatu, SP. Os resultados obtidos revelaram que os painéis estudados tiveram bom desempenho físico, atendendo, no geral, as especificações técnicas estabelecidas pelas normas técnicas, mesmo nos tratamentos com as maiores proporções de adições. O teor de umidade final do painel teve efeito nas propriedades estudadas com tendência generalizada de redução nos valores de absorção de água e inchamento em espessura quando o teor de umidade final do painel aumentou de 9% para 12,5%.
Physical characterization of particleboard panels made from Eucalyptus grandis with addition of industrial wood residues
Keywords: painéis de partículas; MDP; resíduos de madeira; propriedades físicas; particleboard; MDP; wood industries residues; physical properties